Climate-change-driven growth decline of European beech forests - Martinez Del Castillo, Edurne; Zang, Christian S; Buras, Allan; Hacket-Pain, Andrew; Esper, Jan; Serrano-Notivoli, Roberto; Hartl, Claudia; Weigel, Robert; Klesse, Stefan; Resco de Dios, Victor; Scharnweber, Tobias; Dorado-Liñán, Isabel; et al. (Communications biology, 2022)
The growth of past, present, and future forests was, is and will be affected by climate variability. This multifaceted relationship has been assessed in several regional studies, but spatially resolved, large-scale analyses are largely missing so far. Here we estimate recent changes in growth of 5800 beech trees (Fagus sylvatica L.) from 324 sites, representing the full geographic and climatic range of species. Future growth trends were predicted considering state-of-the-art climate scenarios. The validated models indicate growth declines across large region of the distribution in recent decades, and project severe future growth declines ranging from -20% to more than -50% by 2090, depending on the region and climate change scenario (i.e. CMIP6 SSP1-2.6 and SSP5-8.5). Forecasted forest productivity losses are most striking towards the southern distribution limit of Fagus sylvatica, in regions where persisting atmospheric high-pressure systems are expected to increase drought severity. The projected 21st century growth changes across Europe indicate serious ecological and economic consequences that require immediate forest adaptation.
Keywords: období sucha; buk (rod); Climate Change; Fagus; stromy; Trees; Droughts; lesy; klimatické změny; Forests